2020
DOI: 10.1186/s12981-020-00289-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of two POC technologies for CD4 count in Morocco

Abstract: Background: In the era of "test and treat strategy", CD4 testing remains an important tool for monitoring HIVinfected individuals. Since conventional methods of CD4 count measurement are costly and cumbersome, POC CD4 counting technique are more affordable and practical for countries with limited resources. Before introducing such methods in Morocco, we decided to assess their reliability. Methods: In this study 92 blood samples from HIV-infected patients, were tested by PIMA and FACSPresto to derive CD4 count… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The results of both studies indicated the good consistency between these two analysers. It is in agreement with two separate, analogous studies by Elharti et al [23] and Sagnia et al [24] that produced the same results. However, the results obtained by Bwana et al suggest that despite the sufficient…”
Section: Tc Cells [%] -Mean Values -Facscanto II and Facslyric Tc Cel...supporting
confidence: 92%
See 1 more Smart Citation
“…The results of both studies indicated the good consistency between these two analysers. It is in agreement with two separate, analogous studies by Elharti et al [23] and Sagnia et al [24] that produced the same results. However, the results obtained by Bwana et al suggest that despite the sufficient…”
Section: Tc Cells [%] -Mean Values -Facscanto II and Facslyric Tc Cel...supporting
confidence: 92%
“…It is in agreement with two separate, analogous studies by Elharti et al . [ 23 ] and Sagnia et al . [ 24 ] that produced the same results.…”
Section: Discussionmentioning
confidence: 99%
“…It can ultimately help PLWH get their CD4 count test results faster and facilitate their timely initiation into or adjustment to antiviral treatment regimens (9-10). In some countries, studies have shown that adopting POC CD4 detection instruments can meaningfully improve the timeliness of initiating antiviral therapies (6,(11)(12). Timeliness plays a vital role in the care and therapeutic evaluation of HIV patients; this is especially witnessed in mobile HIV testing services (HTS) delivery, which patients are often more willing to use (11).…”
Section: Discussionmentioning
confidence: 99%
“…However, the time and frequency of detection are limited as flow cytometry techniques, which require more time, are the primary means of follow-up detection for PLWH in most areas of China (3)(4)(5). In comparison, some recent studies have shown point of care (POC) technology to positively affect timely treatment and assessment of therapeutic efficacy for HIV (6)(7).…”
mentioning
confidence: 99%
“…Additionally, at this threshold MACS-Countess had PPV and NPV of 96.3% and 85.7%, respectively. The PIMA system has either lower or similar upward misclassification values (0-10.4%) with a sensitivity of 89.6 to 100% [29,30], whereas it has a lower PPV at 91.2% and a higher NPV at 92.3% [31,32]. As the cut-off increases to 500 cells/µL, the specificity of MACS-Countess decreases to 88.9%, whereas the sensitivity remains 89.7%, which are not much different from those of PIMA, which are 95.5% and 84.2%, respectively [30].…”
Section: Macs-countess Compared With Facsmentioning
confidence: 98%